Expression of phenotypic plasticity in hatchlings of the lizard Calotes versicolor (Squamata: Agamidae): influence of nest moisture. - Pandav, Bhagyarekha N.; Saidapur, Srinivas K.; Shanbhag, Bhagyashri A. (Phyllomedusa: Journal of Herpetology, 2012)
Calotes versicolor breed from late May to early October. The breeding activity begins with the onset of the southwestmonsoon. The eggs laid in early breeding season experience more wet conditions than those of the late breeding season. We studied the influence of nest moisture levels on thephenotypic traits of hatchlings by burying the eggs in 5-cm-deep sand nests with ~50% (wet nest) or ~20% (relatively dry nest) moisture to simulate nesting conditions of early and late breeding seasons. A group of eggs were subjected to standard laboratory incubation procedure in which eggs are half-buried in the moist sand and the other half exposed to air. Hatching time and hatchling body size varied with the treatment. The eggs from dry nests hatched later and hatchlings were the biggest but possessed least amount of residual yolk compared to those of ''wet nest'' and also ''lab incubated'' groups. In these hatchlings head and limb sizes were significantly larger than that of the other two groups. The findings show: (1) a developmental plasticity in the lizard, (2) that under low moist conditions larger body size is preferred, and (3) that the trade-off between somatic growth of embryosand future energy reserves (residual yolk) of hatchlings is influenced by the soil moisture in C. versicolor.